2016 President's Plenary International Psycho‐Oncology Society: challenges and opportunities for growing and developing psychosocial oncology programmes worldwide. Issue 9 (26th July 2017) - Travado, Luzia; Bultz, Barry D.; Ullrich, Andreas; Asuzu, Chioma C.; Turner, Jane; Grassi, Luigi; Jacobsen, Paul
Abstract: Consistent with the International Psycho‐Oncology Society's (IPOS) vision and goals, we are committed to improving quality cancer care and cancer policies through psychosocial care globally. As part of IPOS's mission, upon entering "Official Relations" for a second term with the World Health Organization (WHO), IPOS has dedicated much attention to reaching out to countries, which lack formalized psychosocial care programmes. One of IPOS's strategies to accomplish this goal has been to bring psycho‐oncology training programmes to low‐ and middle‐income countries and regions. To this end, the IPOS Board approved a new position on the Board of Directors for a member from a low‐ to middle‐income country (LMIC). The IPOS 2016 President's Plenary focused on challenges and opportunities that exist in growing and developing psychosocial oncology programmes worldwide . The plenary presentations highlight how IPOS and WHO have aligned their goals to help LMICs support cancer patients as an essential element of cancer and palliative care. IPOS country representatives are strongly supported in liaising with national health authorities and with WHO Country Representatives in LMICs. The plenary speakers discussed the role IPOS Federation has taken in building a global network of psychosocial leaders and the impact this had in assisting LMICs in meeting IPOS's psychosocial care objectives. The plenary highlighted the challenges of expanding psychosocial reach into these countries. One significant question remains: Can psychosocial guidelines be adapted to LMICs and regions?